Social interaction in second language acquisition: A case study at a Semarang kindergarten - Chodhori, Mutiara; Hapsari, Christianti Tri (ELT Forum: Journal of English Language Teaching, 2025)
Social interaction plays a critical and foundational role in Second Language Acquisition (SLA), particularly during early childhood when language learning occurs naturally through daily engagement. In multilingual environments such as Indonesia, where children are exposed to more than one language from a young age, the dynamics of social interaction become especially relevant. Despite extensive literature supporting the value of interaction in SLA, limited studies have focused on learners in hybrid, lab school models that combine formal instruction with informal, play-based learning. This study addresses that gap by exploring how social interaction facilitates English language development among children aged 3 to 6 at one kindergarten in the city of Semarang. A qualitative case study approach was adopted, utilizing classroom observations and teacher interviews to gather rich, contextual data. The findings reveal that peer conversations, structured group tasks, and incidental interactions with teachers and visiting foreigners provide essential opportunities for language input, output, and feedback. Teachers’ scaffolding strategies, aligned with Vygotsky’s Zone of Proximal Development, helped students transition from guided participation to independent language use. Nevertheless, challenges such as differing proficiency levels, passive learners, and limited time hindered optimal implementation. The study concludes that fostering interaction-rich environments is essential in early SLA and that effective instructional strategies must be adaptive and inclusive. These insights have important implications for educators, curriculum designers, and policy makers seeking to enhance language development in diverse early education settings, particularly within multilingual and hybrid learning environments.